Tuning the electronic state of Ni/Mo of heterostructure electrocatalyst by interface engineering for water splitting - Fan, Mingsong; Yu, Lijuan; Gao, Lin; Cui, Lili; Dou, Zhiyu (International journal of hydrogen energy, 2025)
The nanocrystalline-amorphous heterogeneous catalyst exhibits satisfied catalytic activity in electrocatalysis, representing a pivotal strategy for devising high-performance dual-functional electrocatalysts. Here, nanosheet-like Ni(OH)2 precursor loaded on carbon cloth (CC) is transformed to nanocrystalline-amorphous heterostructure catalyst. Firstly, by sulfurnation treatment, the heterostructure of MoS2 and NiS2 crystals (NMS) is constructed. Then, the catalyst composed of amorphous Ni1.99Mo6Se2.18S5.82 and crystalline NiSe2 (NMSeS/NSe) is prepared by further calcination treatment. Compared to that of NMS sample, the electronic states of Ni and Mo in the NMSeS/NS sample are modified, resulting in Ni exhibiting a higher electron density and Mo a lower electron density, respectively. Benefiting from the electron interaction between interfaces in NMSeS/NSe sample, the electrochemical surface area (ECSA) is increased and charge transfer resistance (Rct) is reduced. In 1 M KOH, NMSeS/NSe heterostructure only requires low potentials of 62 mV and 216 mV to achieve 10 mA cm−2 for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). The catalyst also exhibits rapid reaction kinetics and near-100 % faraday efficiency (FE). Furthermore, it displays robust stability, with current density degradations of merely 2.4% (HER) and 2.8% (OER) after 120 h of continuous operation. Notably, the NMSeS/NSe catalyst outperforms the NMS sample in both HER and OER. When employed in an electrolyzer for overall water splitting, the NMSeS/NSe electrocatalyst delivers a current density of 10 mA cm−2 at a cell voltage of only 1.42 V, indicative of its superior efficiency. This work introduces a novel bifunctional electrocatalyst developed via precise interfacial engineering. •The crystal NiSe2 and amorphous Ni1.99Mo6Se2.18S5.82 heterostructure is constructed.•The electron state of Ni and Mo can be altered by changing the composition of catalyst.•The heterostructure catalyst shows the fast kinetics for HER/OER.•The heterostructure catalyst only need 1.67 V to get 50 mA cm−2 for EWS.